Mixing iron oxide nanoparticles with different shape and size for tunable magneto-heating performance. Issue 11 (11th March 2021) - Ovejero, Jesus G.; Spizzo, Federico; Morales, M. Puerto; Del Bianco, Lucia
Abstract : An efficient and versatile strategy is presented to modulate the magneto-heating performance of a nanoparticle system, which consists of mixing nanoparticles with different shape and size and exploiting the magnetic interaction between them. Abstract : Tuning the magnetic properties of nanoparticles is a strategic goal to use them in the most effective way to perform specific functions in the nanomedicine field. We report a systematic study carried out on a set of samples obtained by mixing together iron oxide nanoparticles with different shape: elongated with aspect ratio ∼5.2 and mean volume of the order of 10 3 nm 3 (excluding the silica coating) and spherical with mean volume one order of magnitude larger. These structural features of the nanoparticles together with their aggregation state determine the magnetic anisotropy and the magnetic relaxation processes. In particular, the spherical nanoparticles turn out to be more stable against superparamagnetic relaxation. Mixing the nanoparticles in different proportions allows to modulate the magnetic response of the samples. The two populations of nanoparticles magnetically influence each other through a mean field mechanism, which depends crucially on temperature and rules the hysteretic magnetic properties and their thermal evolution. This magnetic phenomenology has a direct impact on the ability of the mixed samples to generate heat under an alternating magnetic field, a key function in view of nanomedicine applications. Under proper testing conditions, the heating efficiency of the mixed samples is larger compared to that obtained as the sum of those of the parent nanoparticles. This occurs thanks to the mean field produced by the magnetically blocked spherical nanoparticles that stabilizes the thermally fluctuating moments of the elongated ones, which therefore contribute more effectively to the heat production.